Handbook of biologically active peptides - Kastin, Abba J. (Elsevier/AP, 2013)
The definitive, indispensable reference for peptide researchers, biochemists, cell and molecular biologists, neuroscientists, pharmacologists, and endocrinologists. Its chapters are designed to be a source for workers in the field and enable researchers working in a specific area to examine related areas outside their expertise. Peptides play a crucial role in many physiological processes, including actions as neurotransmitters, hormones, and antibiotics. Research has shown their importance in such fields as neuroscience, immunology, pharmacology, and cell biology. The second edition of Handbook of Biologically Active Peptides presents this tremendous body of knowledge in the field of biologically active peptides in one single reference. The section editors and contributors represent some of the most sophisticated and distinguished scientists working in basic sciences and clinical medicine.